Information Technology and Growth - Jorgenson, Dale W; Stiroh, Kevin J (American Economic Review, 1999)
The rapid diffusion of information technology (IT) is a direct consequence of the swift decline in the price of computer-related equipment, which has led to a vast and continuing substitution of IT equipment for other forms of capital and labor. This substitution generates substantial returns for the economic agents who undertake IT investments and restructure their activities in order to increase the role of IT. There is little evidence, however, that substitution is accompanied by technical change as this term is used by economists. While this appears highly paradoxical to technologists, who think of substitution of a more IT-intensive mode of production for a less ITintensive mode as a change in technology, it is entirely consistent with the economic framework developed by Robert M. Solow (1957). What do economists mean by ‘‘technical change’’ and how could this exclude the substitution of a more IT-intensive production process for one that is less IT-intensive? Substitution represents movement along a given production function, while technical change corresponds to a shift in the production function. Substitution takes place if the introduction of computer-intensive equipment produces benefits that are fully captured or internalized by the users of IT and their suppliers. Technical change occurs only if more